Rancang Bangun Aplikasi Absensi Online di SMK Menggunakan Framework Laravel - Herisvan Hendra; Haris Kurniawan; Rini Novita; Ami Anggraini Samudra; Widya Islamiah Sibarani; Kuntum Khaira Ummah; Laura Anggraini (Lembaga Yasin AlSys, 2026)
Although attendance management systems have been widely discussed in previous research, studies that specifically examine the implementation of web-based attendance systems using the Laravel framework in vocational high schools remain limited. This study aimed to develop an integrated online attendance system based on the Laravel framework to overcome the limitations of manual attendance methods. A quantitative approach was employed using the Software Development Life Cycle (SDLC) waterfall model and a Model–View–Controller (MVC) architecture. The system was designed for two types of users, namely administrators and participants, with system requirements data collected through direct observation of manual attendance processes to identify sources of inefficiency. The results indicate that the developed system was able to reduce recording errors by up to 95%, increase attendance process efficiency by 40%, and shorten recording time from an average of 12 seconds to 4 seconds per transaction. In addition, data integration across modules achieved 98% consistency with no detected inconsistencies. These findings contribute to the development of web-based information system theory and broaden understanding of Laravel framework implementation in the context of vocational education. The study concludes that adopting a Laravel-based attendance system is an important component of digital transformation in vocational high schools and recommends the implementation of integrated digital attendance solutions as a strategic step toward modernizing attendance management. The implications of this research include theoretical contributions to the literature on web-based system development and practical implications for educational institutions seeking to modernize attendance processes, while also opening opportunities for further studies on biometric integration and mobile application development.